PENGARUH BELANJA MODAL TERHADAP PERTUMBUHAN KINERJA KEUANGAN DAERAH DENGAN PENDAPATAN ASLI DAERAH SEBAGAI VARIABEL INTERVERNING (Studi Kasus Pada Kota dan Kabupaten di Propinsi Jawa Tengah Tahun 2015-2017) - Neilis Sa’Adah; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
This study intends to analyze the effect of Capital Expenditures on the growth of financial performance with Regional Original Income as an intervening variable. In connection with these problems the following hypothesis is proposed: Capital Expenditures affect Regional Original Revenue, Regional Original Revenues have an effect on Growth of Financial Performance, Capital Expenditures have an effect on Growth Financial Performance and Capital Expenditures have an effect on Growth of Financial Performance through Regional Original Income as an intervening variable. In line with these problems and hypotheses, the population of this study is the Realization of Budget Revenue Expenditures in the Regency / City in Central Java Province in 2015-2017 and as a sample of Capital Expenditures, Original Regional Revenues, and variables that are parameters for measuring the financial performance of the Regency / City in Central Java Province. The data used is secondary data, to get more accurate data, the method used is documentation. The analytical method used is descriptive statistics, outer model test and inner model test. Capital Expenditures have a positive and significant effect on Regional Original Revenue, Regional Original Income has a positive and significant effect on Growth of Financial Performance, Capital Expenditures significantly have a direct positive effect on Growth of Financial Performance and Capital Expenditures significantly indirectly has a positive effect on Growth of Financial Performance with Regional Original Income as an intervening variable.